ASHĀB AL-YAMĪN AND ASHĀB AL-SYIMĀL IN QS AL-WĀQI'AH: SEMIOTIC CRITICISM OF ISLAMIC POLARIZATION IN ISLAMIC SOCIAL MEDIA - Muhamad Khabib Imdad; Ahmad Aqiel Azkiya; Muhammad Bayu Fitriansyah; Ina Nabihatul Ulfah (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2025)
This study aims to examine the symbols Ashāb al-Yamīn and Ashāb al-Syimāl in Surah al-Wāqi‘ah through Roland Barthes' semiotic framework and relate them to contemporary religious content on social media that may provoke religious polarization among Indonesian Muslim communities, while also offering a critique of this phenomenon. This research employs a qualitative-descriptive method using library research and digital observation as a case study strategy. Primary data are derived from verses of Surah al-Wāqi‘ah and Islamic social media content, while secondary data consist of classical and contemporary tafsir literature and Barthes' semiotic theory. The findings reveal that the symbols Ashāb al-Yamīn and Ashāb al-Syimāl, at the denotative level, represent eschatological-ethical categories oriented toward deeds and spirituality. However, within the social media sphere, these meanings shift to the connotative level and form ideological myths through their symbolic charge when utilized by certain groups as instruments of truth claims. The right–left dichotomy is reduced to sectarian identity markers, legitimizing exclusivism and exacerbating intra-Muslim conflict. These findings affirm that the uncritical use of such symbols contributes to the flourishing of polarization, resulting in both moral fragmentation and the weakening of Islamic solidarity. Therefore, a more ethical and inclusive da'wah discourse is needed to prevent society from becoming trapped in the logic of digital polarization.